Use of the energy/soil water content relationship for the physical-hydric characterization of soils - Cirino, Cledson Gomes; Guerra, Hugo O. Carvalho (Pesquisa Agropecuaria Brasileira, 1994)
Three different soils (sandy, sandy clay loam and sandy clay) were used to test the use of the soil moisture characteristic curve for the physical-hydric characterization of soils. The obtained results (total porosity, effective porosity, field capacity, permanent wilting point and hydraulic conductivity) were statistically compared with those obtained by laboratory or field conventional methods. The results allow to conclude that the proposed method is a reliable alternative for the determination of the studied parameters.
Keywords: retention curve; porosity; field capacity; wilting point; hydraulic conductivity